MENGHIDUPKAN KEMBALI HAKIKAT NILAI-NILAI PANCASILA - Kuswati, Yeti; Kusmayadi, Dody; Hani RN, Tera Triyantara (Faculty of Social and Political Sciences, Universitas Swadaya Gunung Jati, 2023)
The radical paradigm that tries to change the state ideology considers Pancasila to be the basis of a state that is stupid, humble and selfish. They believe that Pancasila cannot unite a diverse, diverse, ethnic and cultural society. Pancasila, however, is the nation's greatest work. Not forced to follow the